2013
DOI: 10.1002/marc.201300487
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Synthetic Strategies for Core Cross‐Linked Star (CCS) Polymers and Applications as Interfacial Stabilizers: Bridging Linear Polymers and Nanoparticles

Abstract: Core cross-linked star (CCS) polymers become increasingly important in polymer science and are evaluated in many value-added applications. However, limitations exist to varied degrees for different synthetic methods. It is clear that improvement in synthetic efficiency is fundamental in driving this field moving even further. Here, the most recent advances are highlighted in synthetic strategies, including cross-linking with cross-linkers of low solubility, polymerization-induced self-assembly in aqueous-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 116 publications
(182 reference statements)
2
39
1
Order By: Relevance
“…Star polymers with crosslinked polymer cores were prepared via a two stage procedures of two types [32,[152][153][154][155][156]: (i) First, the synthesis of linear polymer chains is performed and then followed by crosslinking of their propagating ends during the addition of a bifunctional monomer and the formation of a nano core of network polymer (the "arm first method"). (ii) At the first stage, a nanogel is formed; at the second stage, it acts as a multi initiator of polymerization of the monofunctional monomer (the "core first method").…”
Section: Discussionmentioning
confidence: 99%
“…Star polymers with crosslinked polymer cores were prepared via a two stage procedures of two types [32,[152][153][154][155][156]: (i) First, the synthesis of linear polymer chains is performed and then followed by crosslinking of their propagating ends during the addition of a bifunctional monomer and the formation of a nano core of network polymer (the "arm first method"). (ii) At the first stage, a nanogel is formed; at the second stage, it acts as a multi initiator of polymerization of the monofunctional monomer (the "core first method").…”
Section: Discussionmentioning
confidence: 99%
“…The historical development of 'arm-first' star polymers, also known as core crosslinked star polymers or star-nanogels, has been reviewed by Blencowe et al (179), Chen et al (180), and Gao and Matyjaszewski (181). In the arm-first process considered here, star assembly and crosslinking take place in a single step involving (co)polymerization of a multi-olefinic monomer mediated by macro-RAFT agent.…”
Section: Star Polymer Synthesis (Core-crosslinked Stars Star-nanogels)mentioning
confidence: 96%
“…In the sequence, we investigated the effect of catalyst concentration for 2@PdNPs (a bottlebrush polymer; Table 3, entries 7-11) and 5@PdNPs (a core-crosslinked star polymer nanogel with bottlebrush arms; Table 3, entries [12][13][14][15][16]. Reactions carried out in presence of 5@PdNPs catalyst system yielded near quantitative conversions for concentrations as low as 1 mol% Pd.…”
Section: Suzuki Coupling Reactionsmentioning
confidence: 99%
“…Consisting of well-defined cross-linked nanoparticles with a water-soluble polymer at the outer shell and an either compact or swollen core, they behave as highly hydrated unimolecular single objects [13][14][15][16] (so-called nanogels) through which reactants and products of organic reactions can diffuse without big constrains. Indeed, Chen et al 14 and Zhang et al 13 formerly pointed out the use of CCS polymers as interfacial stabilizers, which affect colloidal systems to an extent intermediate between soluble polymers and colloidal particles. Previous studies by Seto et al 17,18 showed that the catalytic activity of palladium nanoparticles loaded in nanogels of amino-functionalized polymers was higher than that of bulk palladium, and that such systems can be used to devise continuous-flow Suzuki coupling reactors.…”
Section: Introductionmentioning
confidence: 99%